Biodiversity in Agriculture 2012
DOI: 10.1017/cbo9781139019514.002
|View full text |Cite
|
Sign up to set email alerts
|

Introduction: The Domestication of Plants and Animals: Ten Unanswered Questions

Abstract: Some 15,000 to 10,000 years ago, humans started seeding and harvesting plants and maintaining animals in order to augment the food they obtained from wild-growing plants and hunting. These seemingly simple activities set in motion a long-term process that has led to the dominance of agriculture as we know it today. With the exception of a few remaining hunter-gatherer groups, agriculture has now become the most important source of food for most people. Agriculture is also a major source of feed for animals and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 35 publications
(22 reference statements)
0
14
0
2
Order By: Relevance
“…In Article 2 of the Convention on Biological Diversity (CBD) in-situ conservation is defined as “ the conservation of ecosystems and natural habitats and the maintenance and recovery of viable populations of species in their natural surroundings and, in the case of domesticated or cultivated species, in the surroundings where they have developed their distinctive properties ” [ 34 ]. On-farm conservation of useful species by farmers has been recognized as an in-situ or circa-situ conservation strategy [ 4 , 35 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In Article 2 of the Convention on Biological Diversity (CBD) in-situ conservation is defined as “ the conservation of ecosystems and natural habitats and the maintenance and recovery of viable populations of species in their natural surroundings and, in the case of domesticated or cultivated species, in the surroundings where they have developed their distinctive properties ” [ 34 ]. On-farm conservation of useful species by farmers has been recognized as an in-situ or circa-situ conservation strategy [ 4 , 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…The continuous selection and cultivation of variants of useful species to humans, most often, result in domesticated crops [ 2 , 3 ]. Gepts et al [ 4 ] indicated that the increase in human demand represents new push for domestication. The main advantages of domesticating intensively wild-harvested edible plant species include: (a) enhanced local livelihoods and food security, (b) increased supply of market commodities and maintenance of food diversity, and (c) increased ecosystem services and resilience.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Domestication is one of the most important developments in human history [1]. Beginning during the Late Pleistocene with dog domestication [2,3], it has irrevocably impacted human history, demography, and evolution leading to our current civilizations [1,[4][5][6]. Domesticated species play important roles for humans in many aspects of our daily life by providing food, biological control agents, pets, sporting animals, basic materials, and laboratory models [1,7,8].…”
Section: Introductionmentioning
confidence: 99%